2017
DOI: 10.1021/acs.jpclett.7b00133
|View full text |Cite
|
Sign up to set email alerts
|

Correlatively Dependent Lattice and Electronic Structural Evolutions in Compressed Monolayer Tungsten Disulfide

Abstract: Transition-metal dichalcogenides (TMDs) are promising materials for optoelectronic devices. Their lattice and electronic structural evolutions under high strain conditions and their relations remain open questions. We exert pressure on WS monolayers on different substrates, namely, Si/SiO substrate and diamond anvil surface up to ∼25 GPa. Structural distortions in various degree are disclosed based on the emergence of Raman-inactive B mode. Splits of out-of-plane B and A' modes are only observed on Si/SiO subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 45 publications
7
24
1
Order By: Relevance
“…Whereas for the hBN/WSe 2 -ML/hBN heterostructure both exciton energies increase linearly with increasing pressure with a coefficient of 3.5-3.8 meV/GPa, for the bare WSe 2 ML the excitons decrease in energy with a slope of -3.1 and -1.3 meV/GPa for the A-and B-exciton, respectively. Comparing with the available literature data, the pressure coefficient of the A-exciton determined here for the encapsulated WSe 2 ML is roughly one order of magnitude smaller than the one reported for a single ML of MoS 2 (20 meV/GPa [14], 30 meV/GPa [15], 40 meV/GPa [16], 50 meV/GPa [17]), WSe 2 (32 meV/GPa [19]) and WS 2 (20 meV/GPa [20]). All these data were obtained for monolayers on Si/SiO 2 substrates, where the oxide layer was fairly thick, ranging between 200 and 300 nm.…”
Section: -3contrasting
confidence: 49%
See 3 more Smart Citations
“…Whereas for the hBN/WSe 2 -ML/hBN heterostructure both exciton energies increase linearly with increasing pressure with a coefficient of 3.5-3.8 meV/GPa, for the bare WSe 2 ML the excitons decrease in energy with a slope of -3.1 and -1.3 meV/GPa for the A-and B-exciton, respectively. Comparing with the available literature data, the pressure coefficient of the A-exciton determined here for the encapsulated WSe 2 ML is roughly one order of magnitude smaller than the one reported for a single ML of MoS 2 (20 meV/GPa [14], 30 meV/GPa [15], 40 meV/GPa [16], 50 meV/GPa [17]), WSe 2 (32 meV/GPa [19]) and WS 2 (20 meV/GPa [20]). All these data were obtained for monolayers on Si/SiO 2 substrates, where the oxide layer was fairly thick, ranging between 200 and 300 nm.…”
Section: -3contrasting
confidence: 49%
“…All these data were obtained for monolayers on Si/SiO 2 substrates, where the oxide layer was fairly thick, ranging between 200 and 300 nm. In the work of Han et al [20], the same experiment is reported for a WS 2 ML exfoliated directly onto the diamond and a much smaller pressure coefficient is found (10 meV/GPa). In the next section, we suggest a possible way to explain such a large disparity in the high pressure results concerning the excitonic properties of single MLs on the basis of a close inspection of the stress-strain relations.…”
Section: -3mentioning
confidence: 56%
See 2 more Smart Citations
“…Due to these superior properties, monolayer WS 2 has shown promising applications in electronics, spintronics, valleytronics, and optoelectronic, such as field‐effect transistors, photodetectors, magnetoluminescence devices, and valleytronic devices . Monolayer WS 2 crystal, whose bandgap and lattice vibrations are highly sensitive to external conditions like strain, pressure, temperature, and electric field, is also a perfect model material for PL and Raman studies . Although numerous studies and research on atomically thin WS 2 crystals have been carried out, there has been no experimental observation on WS 2 bubble so far, much less its properties.…”
Section: Introductionmentioning
confidence: 99%